Low-pressure economizer increases fly ash collection efficiency in ESP. (25th January 2016) - Li, Zhi-min; Sun, Feng-zhong; Ma, Lei; Wei, W.; Li, Fei
Highlights: The moisture content of the ash samples increased with temperature reduction. The viscous force of the hopper ash samples increased with temperature reduction. The collection efficiency of the sub-micron and micron grade particles was improved. The ESP collection efficiency was improved when the flue gas deeply cooled. Graphical Abstract: Abstract: A cooling experiment was conducted to determine the effect of deeply cooled low-pressure economizers on fly ash collection efficiency in the electrostatic precipitators (ESPs) in a 670 t/h boiler unit. During the experiment, the gas temperature was reduced from 127 °C to 90 °C by adjusting the loading on the low-pressure economizer, and the ash samples were collected at the flue input and outputs of the ESPs, and the output of ESP hoppers at different temperatures. The moisture content of the ash samples was obtained using the drying test. The microscopic morphology was analyzed using scanning electron microscope (SEM), and the particle size distribution was found using a laser particle size analyzer. The analysis results showed that the moisture content and the viscous forces of the ash samples increased with flue gas temperature reduction. From the SEM scanning, we concluded that the chemical reactions and the agglomeration phenomenon occurred at 95 °C. The median diameter (d50) of the ash samples collected in every ESP hopper decreased significantly. The ESP collection efficiency of particles smaller than 10 µm was significantly improved with the deep cooling of the flue gas, and the dust emission met the requirements of the GB-13223-2011 "Emission standard of air pollutants for thermal power plants."